A Decade of Disaster Experiences in Ōtautahi Christchurch
XXIII, 405 p. 35 illus., 28 illus. in color.
Keywords: This book critically surveys a decade of disasters in Ōtautahi Christchurch. It brings together a diverse range of authors, disciplinary approaches and topics, to reckon with the events that commenced with the 2010-2011 Canterbury earthquake sequence. Each contribution tackles its subject matter through the frame of Critical Disaster Studies (CDS). The events and the subsequent recovery provide a once-in-a-lifetime opportunity to learn from a series of concatenating urban disasters in order to prepare us for our future on an urban planet facing unprecedented environmental pressures. The book focuses on the production of vulnerability, the human dimensions of disaster, the Indigenous response to disasters and the practical lessons that can be drawn from them. .